Selection of coffee progenies of catucaí group - Carvalho, Alex Mendonça; Mendes, Antonio Nazareno; Rezende, Fernando Valaci; Botelho, Cesar Elias; Carvalho, Gladyston Rodrigues; Ferreira, Andre Dominghetti (Coffee Science - ISSN 1984-3909, 2016)
The coffee tree genetic improvement has brought expressive profit to the activity through the use of cultivars with high productivity and favorable agronomic traits. The aim of the improvement programs is gatheningthe best characters in a cultivar. So it searched to select the coffee tree progenies for favorable characteristics of productivity, grains size, vegetative force, resistance to rust and cercospora leaf spot. The experiments were carried out at the EPAMIG Experimental Farm, in TrêsPontas - Minas Gerais, which were used 33 progenies, derived of mix among cultivars of the group Icatu and Catuaí. The square lattice 6x6 with 3 replicates was the experimental designs adopted, and the assessments were made during 4 crops (2009/10, 2010/11, 2011/12 e 2012/13). The characteristics tested were: productivity (bags. ha-1), perceptual of retained fruits in sieves 17 up, notes: vegetative vigor and incidence andseverity of rust. The H6-47-10 Cova 3progenies and H4-35-11 Cv10 show superior productivity to the other progenies and cultivars with favorable characteristics grainsize and plant vigor but were allocated in the group of higher infestationofrust.TheHMSCv13progenies andHMSCv11are note worthy for addition to have a high production and plant vigor is allocated in the group with minor infestation of rust. Regarding the grain size of these two progenies are allocated in the second group along with the commercial cultivars Catuai Amarelo IAC 62 and Catucai Amarelo 2SL.